Drowing 2D in iOS (Technical note) - Hernández-Castro, Franklin (2014)
This paper explains basic concepts that are needed to draw in two dimensions in iOS, in other words, to drawing in two dimensions for iPhone and iPads in the programming language Objective-C. This environment offers several alternatives for this purpose and this article covers the generalities necessary to understand which of them are used in each case. It also offers a couple of examples of how to implement some of these possibilities.